Intracranial intermediate-grade meningeal melanocytoma: A 5-month-old child case report - Wangbin Deng; Guofu Li; Yonkang Zhang (Interdisciplinary Neurosurgery)
Background: Intermediate-grade meningeal melanocytoma (IGM) represents a rare subtype of central nervous system melanocytic tumors, classified as a distinct pathological entity in the 2021 WHO Classification of Central Nervous System Tumors. Pediatric cases, particularly in infants under 1 year of age, are exceedingly rare. Preoperative diagnosis is frequently delayed due to nonspecific clinical manifestations and radiological features overlapping with common pathologies such as gliomas or hemorrhagic lesions. Case report:The older twin brother, a 5-month-old boy, presented with a 3-month history of seizures at our department. Initial evaluation at a local hospital revealed a hyperdense left temporal lobe lesion on computed tomography (CT), misdiagnosed as spontaneous hemorrhage. Subsequent magnetic resonance imaging (MRI) demonstrated a T1-weighted hyperintense, T2-weighted hypointense lesion with mild gadolinium enhancement. Detailed physical examination identified two cutaneous melanocytic lesions. Eelectroencephalography(EEG) showed short bursts of slow waves were observed in the left temporal region in both wakefulness and sleep states; Video-EEG monitoring captured clinical seizures of left temporal origin. In particular, the younger twin had no symptoms. The patient underwent left temporal craniotomy with gross total resection of the lesion. Histopathological analysis confirmed IGM, characterized by bland melanocytic proliferation, rare mitotic figures (<1/10 HPF), and strong immunohistochemical positivity for Melan-A, HMB45, and SOX10. Molecular profiling of the tumor failed to identify known pathogenic mutations. Postoperative recovery was uneventful, and the patient remained seizure-free on sodium valproate throughout a 12-month follow-up period. Discussion: This case highlights the diagnostic complexity of pediatric IGM, emphasizing the importance of integrating multimodal data (clinical, radiological, and histopathological) to differentiate it from hemorrhage or glioma. While MRI features such as T1 hyperintensity and mild enhancement provide clues, definitive diagnosis relies on histopathological confirmation. The absence of symptoms in the monozygotic twin supports a somatic rather than germline origin. Current management prioritizes gross total resection, though adjuvant therapies remain undefined due to limited pediatric data. Further studies are needed to elucidate molecular drivers (e.g., GNAQ/GNA11 mutations) and optimize risk-adapted strategies.